Projections of Mukai varieties - Kapustka, Michał (MATHEMATICA SCANDINAVICA, 2018)
This note is an answer to a problem proposed by Iliev and Ranestad. We prove that the projections of general nodal linear sections of suitable dimension of Mukai varieties $M_g$ are linear sections of $M_{g-1}$.